A clinical study to know the pattern of refractive error in children attending a tertiary care hospital - Kalita, Prasenjit; Dutt, Iku; Boro , Manjit (International Journal of Research in Medical Sciences, 2023)
Background: Refractive error is a major cause of low vision in children. Uncorrected refractive error causes amblyopia, poor school performance and severe visual impairment. The purpose of the present study was to know the pattern of refractive error in children attending a tertiary care hospital. Methods: A hospital based observational retrospective study which was conducted in Gauhati Medical College and Hospital for a period of 15 months from January 2021 to March 2022. 300 children with refractive errors in the age group of 3 years to 15 years were included. Interpretation and analysis of the results were done using appropriate statistical method. Results: Age of presentation of children was more in >10 years to 15 years (51%) followed by 5 years to 10 years (38%). Boys (61.66%) outnumbered girls (38.33%). There was a positive family history of refractive errors (57.33%). More children were found with refractive errors in parents with higher educational qualification. Myopia (49%) was most common followed by astigmatism (43%). Conclusions: Refractive error is a preventable cause of visual impairment. A regular periodic screening for refractive errors should be done in children and it can be corrected simply by prescribing spectacles.